1980
DOI: 10.1063/1.440676
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally inelastic molecule–surface scattering in the sudden approximation

Abstract: Rotational and reorientational transitions in molecular collisions with solid surfaces are investigated by a model based on a sudden approximation with respect to both the rotational and the diffraction states that play a role in the scattering. The approximation developed leads to computationally simple expressions and provides detailed insight into the physical properties of the processes involved. A detailed quantitative study is made of the rotational state distribution produced by the collision, the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The determination of the D 2 diffraction reflectivities requires some additional considerations. It is generally accepted 17,18,22,40 that for inert surfaces the interaction of the molecule with the surface can be separated into the product of a term describing the surface corrugation and another term which accounts for the rotational excitation V͑r,⌰ ͒ϭ͓V 0 ͑ z ͒ϩhV 1 ͑z͒Q͑x,y ͔͓͒1ϩP 2 ͑cos ⌰ ͔͒. ͑5͒…”
Section: B Determination Of Diffraction Reflectivitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the D 2 diffraction reflectivities requires some additional considerations. It is generally accepted 17,18,22,40 that for inert surfaces the interaction of the molecule with the surface can be separated into the product of a term describing the surface corrugation and another term which accounts for the rotational excitation V͑r,⌰ ͒ϭ͓V 0 ͑ z ͒ϩhV 1 ͑z͒Q͑x,y ͔͓͒1ϩP 2 ͑cos ⌰ ͔͒. ͑5͒…”
Section: B Determination Of Diffraction Reflectivitiesmentioning
confidence: 99%
“…RID has in the past been quite extensively investigated both theoretically and experimentally on the surfaces of ionic solids. [17][18][19][20][21] Only a few studies have been reported for H 2 and its isotopes on the low index metal surfaces. For example, RID peaks have been clearly resolved for the anisotropic strongly rotationally coupled HD molecules scattered from the reactive Pt͑111͒ 22 and Ni͑001͒ 23 surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This attribution is in contrast with early theoretical work, which suggested that collisions of H 2 with the surface would be mostly m j conserving. [9][10][11][12][13] In fact, most scattering calculations [11][12][13][14][15][16] performed on this system made use of the potential form introduced by Wolken, 11-13 which contains no dependence on the H 2 azimuthal angle of orientation ͑thereby forbidding ⌬m j transitions͒. On a historical note, it is of interest that Wolken 11 justified the approximate form of his potential by arguing that the LiF surfaces studied at the time 4,5,17 should be covered by H 2 O, which was later shown to be untrue by Estel et al 18 Other calculations 8,9 made use of a hard corrugated wall potential which did contain a dependence on ͑thus allowing ⌬m j transitions͒, but the electrostatic interaction between the quadrupole moment of H 2 and the ionic lattice was not considered in these calculations.…”
Section: Introductionmentioning
confidence: 99%
“…To connect the molecule-surface interaction potential to the inversion symmetry change, the infinite-order sudden approximation, introduced for the scattering of a rigid rotor on a surface by Gerber et ai [19], is used. The scattering operators are written 5/, r =exp[2/77/, r (0,^,0)] ,…”
Section: P--=p + + =(Jkm\[{si + S R )/2v[(si + S R )/2]\jkm)mentioning
confidence: 99%